Compassion in Crisis: Islamic Principles in Disaster Relief - Mohd Perdaus, Ahmad Faizal bin; Kharie, Mohamad Fadli bin; Hasan, Fauziah Mohd (International Journal of Human and Health Sciences (IJHHS), 2025)
The United Nations, through General Assembly Resolutions 46/182 and 58/114, embraced the fundamental principles of humanity, impartiality, neutrality, and independence at the core of all humanitarian actions. These principles are incorporated into the Code of Conduct for the International Red Cross and Red Crescent Movement and Non-Governmental Organizations in Disaster Relief. The principal motivation behind humanitarian action is to save lives and alleviate suffering while upholding and restoring personal dignity. Accordingly, humanity is the principal driver for responding to crises, whether triggered by conflict, violence, or natural or man-made disasters. From the Islamic perspective, humanitarian actions and the duty to help are both considered religious obligations by which all Muslims, rich and poor, are bound. In responding to sufferings, efforts are driven by sincerity (Ikhlas) to God and the need to fulfil obligations to humanity. Hence underlying the above fundamental principles are emphases on excellence (Ihsan), compassion (Rahmah), social justice (Adl), and trust (Amanah). Islam places a strong emphasis on compassion and mercy which are central to the faith and meant to inspire Muslims to act with kindness and empathy towards those in distress. The emphasis on compassion in humanitarian actions is the subject of this presentation. A few instances of compassion in actual humanitarian work experience and their implications are discussed. The fundamental principle of humanity includes compassion but some actual experiences showed the opposite outcomes when humanitarian actions were devoid of sincerity. Finally, practical steps in extending compassion during crisis, such as active listening, offering flexibility and building trust are illustrated. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S16